Method for preparing porous ceramic from high-iron slag
By crosslinking the high-iron slag powder with specific additives, porous ceramics with high flexural strength and through-porosity were prepared, which solved the problem of low flexural strength and porosity when preparing porous ceramics by slag raw materials, and achieved high efficiency , environmentally friendly ceramic material production.
Patent Information
- Application Number
- CN202411384171.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In the preparation process of porous ceramics, using slag with low quality and complex composition as raw materials will reduce the flexural strength and porosity of porous ceramics, limiting the application of slag in the production of porous ceramics.
By ball milling and grinding the high-iron slag powder with methacrylamide, N,N-methylenebisacrylamide and water, a slurry was formed, and ammonium persulfate and N,N,N,N-tetramethyl were added thereto. The mixed liquid of ethylenediamine initiates a cross-linking reaction and improves the curing effect of the slurry, thereby preparing a porous ceramic with high flexural strength and through-porosity.
It has achieved high flexural strength and porosity of high-iron slag ceramic materials, and solved the problem of low flexural strength and porosity when preparing porous ceramics by slag raw materials. It has a simple process, is suitable for large-scale production, reduces production costs, and is green. The social benefits of environmental protection.
Smart Images

Figure CN119390475A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of porous ceramic materials, and in particular relates to a method for preparing porous ceramics by utilizing high-iron slag. Background Art
[0002] As a product of mineral mining and beneficiation, slag is a huge solid waste. If it is not properly handled, it will seriously harm the environment. However, if it can be used as a raw material for some bulk products, it will produce huge economic and social benefits. For example, the chemical composition of slag is similar to that of ceramic raw materials, which makes it possible to use slag in the preparation of porous ceramics. Porous ceramics are a new type of ceramic material that can be widely used in gas or liquid filtration, purification and separation, chemical catalytic carriers, sound absorption and shock absorption, etc., and have great economic value.
[0003] However, in the preparation process of porous ceramics, the composition of the blank has an important influence on the pore size and porosity of the porous ceramics, which in turn affects the performance of the porous ceramic material. Using low-quality and complex slag as raw material to prepare porous ceramics will reduce the flexural strength and porosity of the porous ceramics, which seriously hinders the application of slag in the production of porous ceramics. Summary of the invention
[0004] In view of the above shortcomings, the present invention discloses a method for preparing porous ceramics using high-iron slag, which can not only use high-iron slag as raw material for the production of porous ceramics, but also the obtained porous ceramics have good flexural strength and through-porosity.
[0005] The present invention is achieved by adopting the following technical solutions: A method for preparing porous ceramics using high-iron slag, comprising the following steps: (1) Putting high iron slag powder, methacrylamide, N,N-methylenebisacrylamide and water into a ball mill for grinding, and then passing through a 150-mesh sieve to obtain a slurry, wherein the weight ratio of the high iron slag powder, methacrylamide, N,N-methylenebisacrylamide and water is 100:(2-6):(0.5-3):(30-45); (2) adding ammonium persulfate and N,N,N,N-tetramethylethylenediamine to water in sequence, and then stirring and mixing to obtain a mixed solution, wherein the weight ratio of the ammonium persulfate, N,N,N,N-tetramethylethylenediamine and water is (5-20):(1-10):(10-100), and the weight ratio of the methacrylamide and ammonium persulfate in step (1) is 100:(5-20); (3) adding the mixed solution obtained in step (2) to the slurry obtained in step (1), stirring and mixing until uniformly mixed, and then pouring into a mold, and after the slurry in the mold is solidified, drying and demolding to obtain a green body; adding a mixed solution containing ammonium persulfate and N,N,N,N-tetramethylethylenediamine to a slurry mixed with high-iron slag powder, methacrylamide, N,N-methylenebisacrylamide and water to react, using ammonium persulfate and N,N,N,N-tetramethylethylenediamine to initiate a cross-linking reaction between the high-iron slag powder, methacrylamide and N,N-methylenebisacrylamide, thereby improving the slurry curing effect and thereby improving the strength of the ceramic green body; (4) After drying the green body obtained in step (3), placing it in a kiln for firing, maintaining the temperature at a maximum firing temperature of 1050-1250° C. for 1-3 hours, and cooling it after firing to obtain a porous ceramic.
[0006] Furthermore, the high iron slag powder is obtained by crushing high iron slag, and the particle size of the high iron slag powder is not higher than 300 microns.
[0007] Furthermore, the high iron slag powder includes the following components by mass fraction: 30-55% silicon oxide, 8-18% aluminum oxide, 10-22% ferric oxide, 10-20% calcium oxide, 2-8% magnesium oxide, and other oxides and ignition loss totaling 5-13%. The other oxides include sulfur trioxide, potassium oxide, sodium oxide, manganese oxide, titanium oxide, zinc oxide, etc.
[0008] Furthermore, if the contents of silicon oxide, aluminum oxide, calcium oxide and ferric oxide in the high-iron slag powder do not meet the composition requirements of the high-iron slag powder, natural minerals are added, and the natural minerals are one or more combinations of quartz, clay, limestone and red mud.
[0009] Furthermore, in step (1), the high iron slag powder and water are first put into a ball mill for grinding. When the particle size of the material in the ball mill reaches 20 to 200 microns, methacrylamide and N,N-methylenebisacrylamide are added in sequence and mixed for grinding, and then passed through a 150-mesh sieve to obtain a slurry.
[0010] Furthermore, a foaming agent is added to the slurry obtained in step (1) and stirred and mixed. After a large number of bubbles are formed in the slurry, the mixed solution obtained in step (2) is poured into the slurry, stirred evenly, poured into a mold, and after the slurry in the mold is solidified, it is dried and demolded to obtain a green body. First, a foaming agent is added to the slurry, and then the mixed solution is added to react and solidify. This can ensure sufficient foaming and sufficient operation time, which is conducive to the formation of a porous structure and actual production operation.
[0011] Furthermore, in step (3), the mixed solution obtained in step (2) is added to the slurry obtained in step (1) and stirred and mixed evenly, and then a foaming agent is added and stirred and mixed evenly, so that a large number of bubbles are formed in the slurry, and then poured into a mold. After the slurry in the mold is solidified, it is dried and demolded to obtain a green body, and the weight of the foaming agent is 0.5-8% of the weight of the high-iron slag powder in step (1). The mixed solution is first added to the slurry for reaction, and then the foaming agent is added for foaming treatment, and then solidification is performed, which shortens the time before foaming and bubble solidification, so that the foam is not easy to break after formation, and avoids affecting the formation of a porous structure due to the reduction of foam.
[0012] Furthermore, the foaming agent is one or more combinations of sodium dodecylbenzene sulfonate, hydrogen peroxide, animal protein, plant protein, and triethanolamine lauryl sulfate. The present invention selects a suitable foaming agent and selects a suitable time of addition according to the type and characteristics of the foaming agent, thereby facilitating better foaming effects and promoting the formation of a porous structure.
[0013] Furthermore, the stirring speed in step (2) is 150 to 300 r / min; and the stirring speed in step (3) is 200 to 400 r / min. In step (2), the stirring speed of the mixture of ammonium persulfate, N,N,N,N-tetramethylethylenediamine and water is controlled to promote the rapid dissolution and uniform mixing of ammonium persulfate and N,N,N,N-tetramethylethylenediamine in water; in step (3), due to the different properties of the mixed liquid and the slurry, the stirring speed can be adjusted to promote the rapid and uniform mixing of the two materials, and can promote the interaction of the components in the materials, thereby improving the reaction efficiency.
[0014] Furthermore, in step (4), the green body is placed at 50-80° C. for drying, and the moisture content of the green body after drying is less than 3%. The moisture content of the green body after drying is strictly controlled to be below 3% to avoid cracking of the green body during the subsequent sintering process.
[0015] Compared with the prior art, this technical solution has the following beneficial effects: 1. The macroscopic bubbles in the porous high-iron slag ceramic material prepared by the present invention are interconnected by micropores, thereby having a high apparent porosity (through porosity), which is also one of the characteristics of the porous high-iron slag ceramic material prepared by the present invention. The porous high-iron slag ceramic material prepared by the present invention can be used for ceramic membrane products for filtration, noise reduction products for sound absorption and shock absorption, carrier products for chemical catalysis, special wall materials for construction, etc.
[0016] 2. The porous ceramics produced by the present invention using high-iron slag as raw material can obtain particularly high flexural strength while ensuring high porosity, and can obtain high through-porosity (apparent porosity) without using or with a small amount of pore-forming agent. At the same time, the present invention makes full use of high-iron ore waste slag to produce porous slag ceramic materials with high porosity, high through-porosity and high flexural strength, which solves the problem of reducing the flexural strength and porosity of porous ceramics when slag of poor quality and complex composition is used to prepare porous ceramics.
[0017] 3. The process of the present invention is simple, easy to operate, and highly controllable, and is suitable for large-scale production. In addition, the present invention adopts a large amount of high-iron ore waste slag as raw material to prepare high-porosity porous ceramic materials, and uses the material to manufacture ceramic membrane products, which can greatly reduce the production cost of ceramic membranes. At the same time, through the waste utilization of slag, green, low-carbon and environmentally friendly social benefits can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a 10 μm electron microscope image of the tubular ceramic membrane material obtained in Example 1.
[0019] Figure 2 These are pictures of the green body and fired samples obtained in Example 3. Implementation
[0020] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.
[0021] Example 1: A method for preparing porous ceramics using high-iron slag, comprising the following steps: (1) First, high iron slag powder and water are put into a ball mill for grinding. When the particle size of the material in the ball mill reaches 100 μm, methacrylamide and N,N-methylenebisacrylamide are added in sequence and mixed for grinding. Then, the mixture is passed through a 150-mesh sieve to obtain a slurry. The weight ratio of the high iron slag powder, methacrylamide, N,N-methylenebisacrylamide and water is 100:3.33:0.8:44. The high iron slag powder includes the following components by mass fraction: 43.05% silicon oxide, 11.47% aluminum oxide, 16.88% ferric oxide, 15.53% calcium oxide, 4.52% magnesium oxide, 4.24% sulfur trioxide, and other oxides and loss on ignition totaling 4.31%; the high iron slag powder is obtained by crushing high iron slag, and the particle size of the high iron slag powder is 120 microns; (2) adding ammonium persulfate and N,N,N,N-tetramethylethylenediamine to water in sequence, and then stirring and mixing at a speed of 200 r / min to obtain a mixed solution, wherein the weight ratio of the ammonium persulfate, N,N,N,N-tetramethylethylenediamine and water is 7:3:50, and the weight ratio of the methacrylamide and ammonium persulfate in step (1) is 100:14; (3) adding the mixed solution obtained in step (2) to the slurry obtained in step (1), stirring and mixing at a speed of 300 r / min until the mixture is evenly mixed, and then pouring the mixture into a mold. After the slurry in the mold is solidified, drying and demolding are performed to obtain a green body of a tubular ceramic membrane; (4) The green body is placed at 60°C for drying. The moisture content of the green body after drying is 2%. It is then placed in a kiln for firing. The green body is kept at a maximum firing temperature of 1130°C for 3 hours. After the firing is completed, the green body is cooled to obtain a tubular ceramic membrane. The tubular ceramic membrane has a flexural strength of 120 MPa, an apparent porosity of 46%, an average filtration pore size of 1.5 microns, and an air flux of 200 M 3 / M 2 ·h·ba.
[0022] Example 2: A method for preparing porous ceramics using high-iron slag, comprising the following steps: (1) First, high iron slag powder and water are put into a ball mill for grinding. When the particle size of the material in the ball mill reaches 150 μm, methacrylamide and N,N-methylenebisacrylamide are added in sequence and mixed for grinding. Then, the slurry is passed through a 150-mesh sieve to obtain a slurry. The weight ratio of the high iron slag powder, methacrylamide, N,N-methylenebisacrylamide and water is 100:6:3:30. The high iron slag powder includes the following components by mass fraction: 30% silicon oxide, 8% aluminum oxide, 22% iron oxide, 20% calcium oxide, 8% magnesium oxide, 6% sulfur trioxide, and 6% other oxides and ignition loss in total; the high iron slag powder is obtained by crushing high iron slag, and the particle size of the high iron slag powder is 150 microns; (2) adding ammonium persulfate and N,N,N,N-tetramethylethylenediamine to water in sequence, and then stirring and mixing at a speed of 150 r / min to obtain a mixed solution, wherein the weight ratio of the ammonium persulfate, N,N,N,N-tetramethylethylenediamine and water is 18:9:50, and the weight ratio of the methacrylamide and ammonium persulfate in step (1) is 100:20; (3) Adding a foaming agent to the slurry obtained in step (1) and stirring and mixing at a speed of 300 r / min, so that a large number of bubbles are formed in the slurry, then adding the mixed solution obtained in step (2) to the slurry, stirring and mixing at a speed of 200 r / min until uniform, pouring into a mold, and after the slurry in the mold is solidified, drying and demolding to obtain a porous ceramic sound-absorbing board body; the weight of the foaming agent is 8% of the weight of the high-iron slag powder in step (1); the foaming agent is a combination of hydrogen peroxide and animal protein, and the weight ratio of hydrogen peroxide to animal protein is 5:3; (4) The green body is placed at 50° C. for drying, and the moisture content of the green body after drying is 2%. The green body is then placed in a kiln for firing, and kept at a maximum firing temperature of 1250° C. for 1 hour. After the firing is completed, the green body is cooled to obtain a porous ceramic sound-absorbing board. The porous ceramic sound-absorbing board has a flexural strength of 25 MPa, an apparent porosity of 80%, a specific gravity of 0.5, an average pore size of macroscopic pores (bubbles) of 2 to 3 mm, and an average pore size of microscopic pores of 20 to 40 μm.
[0023] Example 3: A method for preparing porous ceramics using high-iron slag, comprising the following steps: (1) First, high iron slag powder and water are put into a ball mill for grinding. When the particle size of the material in the ball mill reaches 80 microns, methacrylamide and N,N-methylenebisacrylamide are added in sequence and mixed for grinding. Then, the slurry is passed through a 150-mesh sieve to obtain a slurry. The weight ratio of the high iron slag powder, methacrylamide, N,N-methylenebisacrylamide and water is 100:2:0.5:30. The high iron slag powder includes the following components by mass fraction: 55% silicon oxide, 18% aluminum oxide, 10% ferric oxide, 10% calcium oxide, 2% magnesium oxide, 3% sulfur trioxide, and 2% other oxides and ignition loss in total; the high iron slag powder is obtained by crushing high iron slag, and the particle size of the high iron slag powder is 300 microns; (2) adding ammonium persulfate and N,N,N,N-tetramethylethylenediamine to water in sequence, and then stirring and mixing at a speed of 200 r / min to obtain a mixed solution, wherein the weight ratio of the ammonium persulfate, N,N,N,N-tetramethylethylenediamine and water is 15:3:35, and the weight ratio of the methacrylamide and ammonium persulfate in step (1) is 100:5; (3) Add the mixed solution obtained in step (2) to the slurry obtained in step (1), and then stir and mix at a speed of 350 r / min. Then add a foaming agent and continue to stir and mix until a large number of bubbles are formed in the slurry. Then pour it into a mold. After the slurry in the mold is solidified, dry and demold to obtain a green body of a porous ceramic wall lightweight brick. Figure 2The weight of the foaming agent is 5% of the weight of the high iron slag powder in step (1); the foaming agent is a combination of sodium dodecylbenzene sulfonate and triethanolamine laurel sulfate, and the weight ratio of the sodium dodecylbenzene sulfonate to triethanolamine laurel sulfate is 2:3; (4) The green body is placed at 70°C for drying, and the moisture content of the green body after drying is 2.5%. It is then placed in a kiln for firing, and kept at a maximum firing temperature of 1200°C for 2 hours. After the firing is completed, it is cooled to obtain a porous ceramic wall lightweight brick, see Figure 2 The porous ceramic wall lightweight brick has a flexural strength of 20 MPa, an apparent porosity of 70%, a specific gravity of 0.65, an average pore size of macroscopic pores (bubbles) of 0.3 to 1.5 mm, and an average pore size of microscopic pores of 30 to 50 μm.
[0024] Example 4: A method for preparing porous ceramics using high-iron slag, comprising the following steps: (1) A high-iron slag was selected, whose chemical composition was: silicon oxide 16.58%, aluminum oxide 6.48%, ferric oxide 27.57%, calcium oxide 13.97%, titanium oxide 4.14%, sodium oxide 0.65%, and other oxides and ignition loss totaled 30.61% , since the contents of silicon oxide, aluminum oxide and ferric oxide deviate from the composition range of the high-iron slag powder, namely: 30-55% silicon oxide, 8-18% aluminum oxide, 10-22% ferric oxide, and 10-20% calcium oxide, in order to make the chemical composition of the slag meet the use requirements, 300 kg of clay, 80 kg of quartz, and 100 kg of limestone are added to 1 ton of slag, and the average particle fineness reaches 80 microns after ball milling and mixing. The main chemical composition of the composite slag after formulation and processing is: 31.44% silicon oxide, 12.35% aluminum oxide, 18.63% ferric oxide, and 13.36% calcium oxide, which meets the chemical composition requirements for preparing porous high-iron slag ceramics; (2) grinding the composite high-iron slag powder, methacrylamide, N,N-methylenebisacrylamide and water prepared in step (1) in a ball mill, and then passing through a 150-mesh sieve to obtain a slurry, wherein the weight ratio of the high-iron slag powder, methacrylamide, N,N-methylenebisacrylamide and water is 100:4:1.5:37; (3) adding ammonium persulfate and N,N,N,N-tetramethylethylenediamine to water in sequence, and then stirring and mixing at a speed of 300 r / min to obtain a mixed solution, wherein the weight ratio of the ammonium persulfate, N,N,N,N-tetramethylethylenediamine and water is 2:1:10, and the weight ratio of the methacrylamide and ammonium persulfate in step (2) is 10:1; (4) adding the mixed solution obtained in step (3) to the slurry obtained in step (2), stirring and mixing at a speed of 400 r / min, and then adding a foaming agent and continuing to stir and mix until a large number of bubbles are formed in the slurry, and then pouring it into a mold. After the slurry in the mold is solidified, drying and demolding are performed to obtain a green body of a porous ceramic catalyst carrier; the weight of the foaming agent is 0.75% of the weight of the composite high-iron slag powder in step (2); the foaming agent is a combination of sodium dodecylbenzene sulfonate and vegetable protein, and the weight ratio of the sodium dodecylbenzene sulfonate to the vegetable protein is 1:1.5; (5) The green body is placed at 80°C for drying. The moisture content of the green body after drying is 2.5%. It is then placed in a kiln for firing. The green body is kept at a maximum firing temperature of 1050°C for 3 hours. After the firing is completed, it is cooled to obtain a porous ceramic catalyst carrier. The porous ceramic catalyst carrier has a flexural strength of 18 MPa, an apparent porosity of 63%, a specific gravity of 0.75, an average pore size of macroscopic pores (bubbles) of 0.1 to 0.5 mm, and an average pore size of microscopic pores of 20 to 40 μm.
[0025] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing porous ceramics using high-iron slag, characterized in that: The following steps are involved: (1) Putting high iron slag powder, methacrylamide, N,N-methylenebisacrylamide and water into a ball mill for grinding, and then passing through a 150-mesh sieve to obtain a slurry, wherein the weight ratio of the high iron slag powder, methacrylamide, N,N-methylenebisacrylamide and water is 100:(2-6):(0.5-3):(30-45); (2) adding ammonium persulfate and N,N,N,N-tetramethylethylenediamine to water in sequence, and then stirring and mixing to obtain a mixed solution, wherein the weight ratio of the ammonium persulfate, N,N,N,N-tetramethylethylenediamine and water is (5-20):(1-10):(10-100), and the weight ratio of the methacrylamide and ammonium persulfate in step (1) is 100:(5-20); (3) adding the mixed solution obtained in step (2) to the slurry obtained in step (1), stirring and mixing until uniformly mixed, and then pouring into a mold. After the slurry in the mold is solidified, drying and demolding are performed to obtain a green body; (4) After drying the green body obtained in step (3), placing it in a kiln for firing, maintaining the temperature at a maximum firing temperature of 1050-1250° C. for 1-3 hours, and cooling it after firing to obtain a porous ceramic.
2. The method for preparing porous ceramics using high iron slag according to claim 1, characterized in that: The high iron slag powder is obtained by crushing high iron slag, and the particle size of the high iron slag powder is not higher than 300 microns.
3. The method for preparing porous ceramics using high iron slag according to claim 1, characterized in that: The high iron slag powder comprises the following components in mass fractions: 30-55% silicon oxide, 8-18% aluminum oxide, 10-22% ferric oxide, 10-20% calcium oxide, 2-8% magnesium oxide, and other oxides and ignition loss totaling 5-13%.
4. The method for preparing porous ceramics using high iron slag according to claim 3, characterized in that: If the contents of silicon oxide, aluminum oxide, calcium oxide and ferric oxide in the high-iron slag powder do not meet the composition requirements of the high-iron slag powder in claim 3, natural minerals are added, and the natural minerals are one or more combinations of quartz, clay, limestone and red mud.
5. The method for preparing porous ceramics using high iron slag according to claim 1, characterized in that: In step (1), high iron slag powder and water are first put into a ball mill for grinding. When the particle size of the material in the ball mill reaches 20 to 200 microns, methacrylamide and N,N-methylenebisacrylamide are added in sequence and mixed for grinding, and then sieved through a 150-mesh sieve to obtain a slurry.
6. The method for preparing porous ceramics using high iron slag according to claim 1, characterized in that: A foaming agent is added to the slurry obtained in step (1) and stirred to form a large number of bubbles in the slurry. Then, the mixed solution obtained in step (2) is poured into the slurry, stirred evenly, and poured into a mold. After the slurry in the mold is solidified, it is dried and demolded to obtain a green body.
7. The method for preparing porous ceramics using high iron slag according to claim 1, characterized in that: In step (3), the mixed solution obtained in step (2) is added to the slurry obtained in step (1) and stirred and mixed evenly, and then a foaming agent is added and stirred and mixed evenly, so that a large number of bubbles are formed in the slurry, and then poured into a mold. After the slurry in the mold is solidified, it is dried and demolded to obtain a green body, and the weight of the foaming agent is 0.5 to 8% of the weight of the high-iron slag powder in step (1).
8. The method for preparing porous ceramics using high iron slag according to claim 6 or 7, characterized in that: The foaming agent is one or more combinations of sodium dodecylbenzene sulfonate, hydrogen peroxide, animal protein, plant protein, and triethanolamine lauryl sulfate.
9. The method for preparing porous ceramics using high iron slag according to claim 1, characterized in that: The stirring speed in step (2) is 150 to 300 r / min; the stirring speed in step (3) is 200 to 400 r / min.
10. The method for preparing porous ceramics using high iron slag according to claim 1, characterized in that: In step (4), the green body is placed at 50-80° C. for drying, and the moisture content of the green body after drying is less than 3%.
Citation Information
Patent Citations
Foamed ceramic and preparing method thereof
CN106045560A
Method for preparing iron tailing porous ceramic through foam-gelcasting / low-temperature sintering
CN106830989A
Method for preparing high-performance porous ceramics from iron tailings
CN112745101A
Manufacturing method for ceramic porous body, and ceramic porous body
JP2005239471A
The preparation of porous ceramics by using foamingprocess
KR1020010056771A